0],\\ e^x-1=0, e^x=1, e^x=e^0, x=0, \\ e^x+1=0, e^x=-1<0, x\in\varnothing \ [e^x>0, e^x+1>0];\\ x<0, e^x<1, e^x-1<0, f'(x)<0, f(x)\searrow \ , \\x>0, e^x>1, e^x-1>0, f'(x)>0, f(x)\nearrow \ , \\ x_{min}=0, y_{min}=f(0)=e^0+e^0=1+1=2. \\ (0;2)" alt="f(x)=e^x+e^{-x}, \\ f'(x)=(e^x+e^{-x})'=(e^x)'+(e^{-x})'=e^x+e^{-x}\cdot(-x)'= \\ =e^x+e^{-x}\cdot(-1)=e^x-e^{-x} \\ \\ f'(x)=0, e^x-e^{-x}=0, \\ e^{-x}(e^{2x}-1)=0, \\ e^{-x}(e^x-1)(e^x+1)=0, \\ e^{-x}=0, x\in\varnothing \ [e^{-x}>0],\\ e^x-1=0, e^x=1, e^x=e^0, x=0, \\ e^x+1=0, e^x=-1<0, x\in\varnothing \ [e^x>0, e^x+1>0];\\ x<0, e^x<1, e^x-1<0, f'(x)<0, f(x)\searrow \ , \\x>0, e^x>1, e^x-1>0, f'(x)>0, f(x)\nearrow \ , \\ x_{min}=0, y_{min}=f(0)=e^0+e^0=1+1=2. \\ (0;2)" align="absmiddle" class="latex-formula">